Зловещий брак: [роман] / М. Брент ; [пер. с англ. З. Зафировой] - Брент Мэйдлин (Дикая орхидея, 1998)
Экземпляры: аб. (1999) / Инвентарный номер: 41247 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: Б 87 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44